Absence of Thiol-Disulfide Oxidoreductase DsbA Impairs cbb3-Type Cytochrome c Oxidase Biogenesis in Rhodobacter capsulatus - Onder, Ozlem; Verissimo, Andreia F.; Khalfaoui-Hassani, Bahia; Peters, Annette; Koch, Hans-Georg; Daldal, Fevzi (Frontiers in Microbiology, 2017)
The thiol-disulfide oxidoreductase DsbA carries out oxidative folding of extra-cytoplasmic proteins by catalyzing the formation of intramolecular disulfide bonds. It has an important role in various cellular functions, including cell division. The purple non sulfur bacterium Rhodobacter capsulatus mutants lacking DsbA show severe temperature-sensitive and medium-dependent respiratory growth defects. In the presence of oxygen, at normal growth temperature (35 oC), DsbA– mutants form colonies on minimal medium, but they do not grow on enriched medium where cells elongate and lyse. At lower temperatures (i.e., 25 oC), cells lacking DsbA grow normally in both minimum and enriched media, however, they do not produce the cbb3-type cytochrome c oxidase (cbb3-Cox) on enriched medium. Availability of chemical oxidants (e.g., Cu2+ or a mixture of cysteine and cystine) in the medium becomes critical for growth and cbb3-Cox production in the absence of DsbA. Indeed, addition of Cu2+ to the enriched medium suppresses, and conversely, omission of Cu2+ from the minimal medium induces, growth and cbb3-Cox defects. Alleviation of these defects by addition of redox-active chemicals indicates that absence of DsbA perturbs cellular redox homeostasis required for the production of an active cbb3-Cox, especially in enriched medium where bioavailable Cu2+ is scarce. This is the first report describing that DsbA activity is required for full respiratory capability of R. capsulatus, and in particular, for proper biogenesis of its cbb3-Cox. We propose that absence of DsbA, besides impairing the maturation of the c-type cytochrome subunits, also affects the incorporation of Cu into the catalytic subunit of cbb3-Cox. Defective high affinity Cu acquisition pathway, which includes the MFS-type Cu importer CcoA, and lower production of the c-type cytochrome subunits lead together to improper assembly and degradation of cbb3-Cox.